Optimalisasi User Interface dan User Experience Aplikasi Whoosh dengan Design Thinking dan UEQ - Wijaya, Dhanny Hidayat; Pinem, Sanjaya; Ridwan, Muhamad (JATISI, 2025)
Mobile applications play a crucial role in the modern transportation sector, including Whoosh – Indonesia High-Speed Rail, which provides ticket booking and travel information services. Despite a high number of downloads, the application has received low ratings, indicating issues related to its UI/UX. This study aims to enhance the quality of the interface and user experience through a Design Thinking approach, involving stages of empathy, problem definition, ideation, prototyping, and testing. An initial evaluation using the User Experience Questionnaire (UEQ) with 46 users identified problems such as confusing navigation, a non-intuitive booking flow, and the lack of a direct assistance feature. The redesign focused on simplifying the interface, implementing OTP-based login, and adding a live chat feature. Follow-up testing showed significant improvements across all UX aspects, with average scores falling into the "Good" to "Excellent" categories. These results indicate that the redesign of the Whoosh application successfully enhanced user satisfaction and supports the image of an efficient and modern transportation service.